Strengthening Multicultural Law in Building Inclusive and Just Legal Systems - Rajarshi Dasgupta (ILAW, 2025)
This study analyzes the role of multicultural law in strengthening inclusive and just legal systems. The research aims to examine how multicultural legal principles are applied in plural societies and how they contribute to justice, equality, and social cohesion. A normative legal research method is used with conceptual and comparative approaches, based on secondary data from legal literature, academic sources, and policy documents. The findings show that multicultural law supports the recognition of cultural diversity, protects minority rights, and enhances access to justice. However, challenges such as legal pluralism tensions and differences in cultural interpretations of justice remain significant obstacles. The study concludes that strengthening multicultural law requires a balanced integration of cultural values into national legal systems supported by strong institutional frameworks.